Incremento en ventas de jugoso al sartén® maggi® a través del conocimiento y prueba del producto por parte del consumidor (2021)
The present work aims to identify key variables for the increase in sales of Jugoso al Sartén® through generating brand awaerness (Brand recognition), Jugoso al Sartén® is a MAGGI® product from Nestlé, launched at the end of 2018, Without the accompaniment of aggressive launch campaigns, which led to the goals in terms of sales established for the first year not being met, an initial diagnosis is made through a SWOT matrix, which allows the following approach Question: How can Jugoso al Sartén® sales be increased taking into account the current levels of brand recognition and consumer proof? As a support for developing the question posed, it was initially necessary to locate the product / brand in the Bowman's strategic watch which allowed determining that it is located on route N ° 4 which was supported in broad theory on innovation as this is one of the characteristics s of the product, and finally seeking to internalize this main attribute in the mind of the consumer through Brand Awaerness; Three different research methods were used that yielded pertinent information to recommend, among other things, the implementation of an aggressive campaign that seeks to increase Brand Awaerness in current consumers through successful communication, advertising focused on the target market, diversification of sales platforms entering in stores preferably located in the sectors where the people of the target segment live.